Living Donor Liver Transplantation in a Korean Child with Glycogen Storage Disease Type IV and a GBE1 Mutation (Gut and Liver, 2009)
Glycogen storage disease type IV (GSD-IV) is an autosomal recessive disease caused by a deficient glycogen branching enzyme (GBE), encoded by the GBE1 gene, resulting in the accumulation of abnormal glycogen deposits in the liver and other tissues. We treated a 20-month-old girl who presented with progressive liver cirrhosis and was diagnosed with GSD-IV, as confirmed by GBE1 gene mutation analysis, and underwent living related heterozygous donor liver transplantation. Direct sequencing of the GBE1 gene revealed that the patient was compound heterozygous for a known c.1571G＞A (p.Gly264Glu) mutation a novel c.791G＞A (Arg524Gln) mutation. This is the first report of a Korean patient with GSD-IV confirmed by mutation analysis, who was treated successfully by liver transplantation. (Gut and Liver 2009;3:60-63)